Folklore, Nonhuman Animals and Social Darwinism - Mathur, Nidhi; Ray, Shailesh Kumar (Ethnographica et Folkloristica Carpathica, 2023)
This article deals with the critical analysis of the selected Grimm’s fairy tales in the context of social Darwinism. First, a brief overview of the term and its historical background is provided. Furthermore, this article looks at various ideas that social Darwinian thinkers have used and presented over time. After that, the article will present the connection between social Darwinism and Grimm's fairy tales. The fairy tales of the Brothers Grimm included in the analysis include: The Fox and the Cat, The Wolf and the Fox, The Wren and the Bear. The fairy tales selected are viewed in this article through the lens of the ‘theriocentric-animalist perspective’, since the anthropocentric reading provides fairy tale animals only in terms of 'character masks of human characteristics', hence the fairy tale animals are forced to 'disappear'. This article argues that the Grimm’s Märchen are antithesis to ‘survival of the fittest’.